BIOLOGI Sitophilus oryzae dan Sitophilus zeamais (COLEOPTERA; CURCULIONIDAE) PADA BERAS DAN JAGUNG PIPILAN - Manueke, Jusuf; Tulung, Max; Mamahit, J. M.E. (Universitas Sam Ratulangi, 2015)
ABSTRACT Â This study aims to determine the biological of Sitophilus oryzae and S. zeamais which includes development stadia, life cycle, long life, fecundity, mortality and sex ratio. Research using descriptive and substitutional methods. The research conducted in the laboratory of Entomology and Plant Pests and Pest Department of Pest and Disease Faculty of Agriculture Sam Ratul;angi University Manado. The results showed differences in the life cycle, long life and fecundity between S. oryzae and S. zeamais. Long life cycle and life imago S. oryzae shorter than S. zeamais. The life cycle of S. oryzae is 35.22 days and S. zeamais 49.13 days. Life long female imago S. oryzae 101 days and 88.75 days males, S. zeamais females and males 109.25 125.75 day day. Fecundity of S. oryzae lower than S. zeamais namely S. oryzae average 152.8 points and S. zeamais average of 203.0 points. Pradewasa mortality and sex ratio of S. oryzae and S. zeamais unchanged at S. oryzae 80.5% and 0.79, S. zeamais 77.0% and 0.77. Keywords: Sitophilus oryzae, Sitophilus zeamais, development stadia, life cycle, long life, Â fecundity, mortality